Cooling of Photovoltaic Panels to Improve Its Efficiency: A Comprehensive Review - Kumar Gupta, Varun (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 8 No 2 (2024): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2024)
Continuous increase in energy demand has led to reduction of fossil fuels and increase in carbon emissions. This brings two-fold problems one is high energy price and second is greenhouse effect. Solar energy has the potential to mitigate both these problems simultaneously as it is clean and freely available. Solar energy can be utilized in two forms – solar thermal and solar photovoltaic (PV). In last one decade lot of progress has been made in the efficiency of PV panels which made them highly cost effective. However, heating is one major drawback of these panels as heating reduces the efficiency of PV panels. Lot of research has been done in the last decade to reduce the heating of PV panels and thus increase the efficiency of panels. This review paper summarizes the work done in the last 10 years related to cooling of PV panels and achieving high efficiency. Lot of different arrangements has been proposed by the researchers and validated either through experimentation or simulation. This paper has covered all cooling technologies developed and implemented in PV panels for effective cooling and achieving higher efficiency.